FORMATION AND STABILITY OF SCHWERTMANNITE IN ACIDIC MINING LAKES - Regenspurg S.; Brand A.; Peiffer S. (My University, 2004)
Schwertmannite (ideal formula: Fe8O8(OH)6SO4) is typically found as a secondary iron mineral in pyrite oxidizing environments. In this study, geochemical constraints upon its formation are established and its role in the geochemical cycling of iron between reducing and oxidizing conditions are discussed. The composition of surface waters was analyzed and sediments characterized by X-ray diffraction, FTIR spectroscopy and determination of the Fe:S ratio in the oxalate extractable fraction from 18 acidic mining lakes. The lakes are exposed to a permanent supply of pyritegenous ferrous iron from adjacent ground water. In 3 of the lakes the suspended matter was fractionated using ultra filtration and analyzed with respect to their mineral composition. In addition, stability experiments with synthetic schwertmannite were performed. The examined lake surface waters were O2-saturated and have sulfate concentrations (10.3 ± 5.5 mM) and pH values (3.0 ± 0.6) that are characteristic for the stability window of schwertmannite. Geochemical modeling implied that i) the waters were saturated with respect to schwertmannite, which controlled the activity of Fe3+ and sulfate, and ii) a redox equilibrium exists between Fe2+ and schwertmannite. In the uppermost sediment layers (1 to 5 cm depth), schwertmannite was detectable in 16 lakes—in 5 of them by all three methods. FTIR spectroscopy also proved its occurrence in the colloidal fraction (1–10 kDa) in all of the 3 investigated lake surface waters. The stability of synthetic schwertmannite was examined as a function of pH (2–7) by a 1-yr experiment. The transformation rate into goethite increased with increasing pH. Our study suggests that schwertmannite is the first mineral formed after oxidation and hydrolysis of a slightly acidic (pH 5–6), Fe(II)-SO4 solution, a process that directly affects the pH of the receiving water. Its occurrence is transient and restricted to environments, such as acidic mining lakes, where the coordination chemistry of Fe3+ is controlled by the competition between sulfate and hydroxy ions (i.e. mildly acidic).
Keywords: Schwertmannite